Lingvosemiotic Content ofLinguistic Features ofThe Speech Genre “Wish” - Sayfutdinova Durdona Pulatjonovna (Global Scientific Publishing, 2024)
In the article, the linguistic features of the speech genre “wish” in the language system are characterized by socio-semiotic content, which has a religious nature, and the features of its implementation with the content of desire in various social situations
Keywords: linguistic attributes; linguosemiotic content; semiotic sign